2007
DOI: 10.1007/s11627-007-9046-5
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in Agave tequilana Weber cultivar azul

Abstract: Somatic embryogenesis was achieved from leaves of Agave tequilana Weber cultivar azul utilizing MS medium supplemented with L2 vitamins and the addition of cytokinins: 6-benzylaminopurine (BA), 1-phenyl-3(1,2,3-thiadiazol-5-yl)urea (TDZ), 6-(γ-γ-dimethylamino)purine (2ip) and 6-furfurylaminopurine (KIN), combined with the auxin 2,4-dichlorophenoxyacetic acid (2,4-D). Differences among the six genotypes studied with regard to their embryogenic response in culture were found. Embryos produced by genotype S3 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 28 publications
8
37
0
5
Order By: Relevance
“…Like their zygotic counterparts, somatic embryos have a single cell origin (Rao, 1996). The single cell origin of somatic embryos has been elegantly reported by several authors, in particular, this unicellular origin of somatic embryos has been reported in Agave tequilana (Gutiérrez-Mora et al, 2004;Portillo et al, 2007).…”
Section: Somatic Embryogenesismentioning
confidence: 87%
See 1 more Smart Citation
“…Like their zygotic counterparts, somatic embryos have a single cell origin (Rao, 1996). The single cell origin of somatic embryos has been elegantly reported by several authors, in particular, this unicellular origin of somatic embryos has been reported in Agave tequilana (Gutiérrez-Mora et al, 2004;Portillo et al, 2007).…”
Section: Somatic Embryogenesismentioning
confidence: 87%
“…In this revision the cellular process is illustrated by the formation of a somatic embryo of Agave tequilana Weber cultivar Azul (Gutiérrez-Mora et al, 2004;Portillo et al, 2007).…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…Our results are similar to those reported by Robert et al (1987) since using 0.11 μM of 2,4-D obtained callus in A. sisalana. Numerous studies have shown that 2,4-D induces somatic embryogenesis in many plant species (Aviles-Viñas et al 2012, Portillo et al 2007, Santana-Buzzy et al 2009, Zapata-Castillo et al 2007, Zuo et al 2002. However, the 2,4-D concentration used is a critical factor.…”
Section: Discussionmentioning
confidence: 99%
“…K. Schum., Portillo et al, (2007) (Correia e Canhoto, 2010). A formação, ou não, de uma estrutura semelhante ao suspensor pode estar relacionada a diferentes origens dos embriões somáticos, podendo o mesmo apresentar uma origem unicelular, que geralmente forma um suspensor, ou terem origem multicelular, não formando essa estrutura, sendo apenas provenientes de um grupo de células, que estão ligadas ao tecido da planta-mãe por uma ampla região (Williams e Maheswaran, 1986).…”
Section: Discussionunclassified